Study on the Crack Propagation Life of the High-speed Train Gear - Li Gang; Li Xiuhong; Ren Jiajun; Qin Xiaofeng; Pang Yinming (Jixie chuandong, 2017)
The crack propagation characteristic property of the high-speed train gears is researched,the location of crack initiation is determined by a statics analysis and building gear pair model in the ABAQUS software.A finite element model of helical gear pair with crack at tooth root is established by ABAQUS software,then the stress intensity factor of the different nodes of crack tip is calculated based on the theory of linear elastic fracture mechanics.Then,the way and the growth trajectory of the crack is studied,the propagation life of the crack at tooth root are obtained by calculation.Based on the obtained result,the influence of load magnitude and other factors on the crack propagation life is discussed.The study indicate that the crack expands slowly at first and then faster and faster,the influence of load magnitude on the crack propagation life is obvious.